The Emergence and Role of Client Perspectives in and on Cancer Treatment - Forchhammer, Hysse Birgitte (Outlines. Critical Practice Studies, 1999)
This paper is divided into two parts: in part one I give some examples from a study of how patient or client perspectives on treatment and life with cancer are “discovered”, addressed, included and shaped within cancer research and treatment after World War 2. In this first part I draw on analyses from my Ph.D. thesis about the concept of quality of life and psycho-social research on cancer, in which I focused on the development and interrelationships between (1) welfare state forms of governance, (2) the practice of cancer treatment and its relation to research, and (3) client’s relations to treatment regimes and a life with cancer. I argue that the client’s perspective is represented in medical practice in many different, and often problematic, ways. A core problem is that this perspective is often represented from a third-person point of view, not from a direct first-person point of view. I find a number of reasons for this. The lack of first-person involvement is not isolated to medical practice but is also obvious in psycho-social practice that evolves in the relation to medical treatment and research in the last part of this century. The conflict around this is reflected in psychological theories about illness and disease that are formulated in this period. In the second part of the article I discuss the directions in which psychological theory has to develop in order to contribute to the recognition and involvement of first-person perspectives in medical treatment and research. The aim of this discussion is not limited to understanding how we as subjects handle everyday life with biological changes of bodily function.